Penciptaan Ragam Hias Tingang Haguet sebagai Alternatif Brand Identity Kabupaten Pulang Pisau Kalimantan Tengah - Olav Iban (Universitas Gadjah Mada, 2014)
Pulang Pisau is a 12 years old division regency in Central Kalimantan Province. Themagnitude opportunities of tourism sector require the local government and variousrelevant stakeholders to developed their regional identity through brand identity. DayakNgaju, the biggest and dominant indigenous group in Pulang Pisau Regency, has thestand out cultural aspects and be able to represent the regency. The representation isfi ltered and merged into a visual form. The landscape aspect of Pulang Pisau Regency,like Kahayan and Sebangau rivers, also plays a main role in contributing the distinctivecharacter. This paper is an attempt to build a brand identity of Pulang Pisau Regencythrough a simple study of the cultural identity of their local community. The result is anornament named Tingang Haguet.